1988
DOI: 10.1073/pnas.85.24.9699
|View full text |Cite
|
Sign up to set email alerts
|

Role of interleukin 1 in the activation of T lymphocytes.

Abstract: The activation of T lymphocytes requires their stimulation via clonotypic antigen receptors as well as nonantigen-specific costimulators, the best defined of which is the cytokine interleukin 1 (IL-1). Recent studies have shown that murine CD4+ helper T lymphocytes consist of two nonoverlapping subsets that selectively utilize interleukin 2 (IL-2) or interleukin 4 as their autocrine growth factors and are called Thl and Th2 cells, respectively. We now show that ILfunctions as a costimulator for the proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
118
2

Year Published

1992
1992
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(128 citation statements)
references
References 26 publications
8
118
2
Order By: Relevance
“…Some reports suggest that IL-1 promotes proliferation of Th2 cells in vitro [14][15][16][17], while others suggest that in the absence of IL-1 signaling, exaggerated Th2 responses occur [18]; again others report no differences [19]. We have found that the absence of either IL-1a or IL-1b results in incomplete Th2 polarization both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Some reports suggest that IL-1 promotes proliferation of Th2 cells in vitro [14][15][16][17], while others suggest that in the absence of IL-1 signaling, exaggerated Th2 responses occur [18]; again others report no differences [19]. We have found that the absence of either IL-1a or IL-1b results in incomplete Th2 polarization both in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 47%
“…Previous work suggests that IL-1a acts as a proliferation stimulus for Th cells [15,16,21,22]. To investigate if the decreased Th2 cytokine production in T. muris-infected IL-1a and IL-1b KO mice was related to reduced proliferation, we measured antigen-and mitogen-induced proliferation by [ 3 H]thymidine incorporation.…”
Section: Antigen-specific Proliferation Is Unaltered In Il-1a and Il-mentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14] Cytokines in the IL-1 system (IL-1␣, IL-1␤ and IL-1 receptor antagonist (IL-1Ra)) are produced at the maternal-fetal interface during early pregnancy. 15 The IL-1 system may be involved in the regulation of Th1/Th2 cytokine production, since IL-1 can function as a costimulator for Th2 cell generation in both rodents and humans [16][17][18][19] and may influence IFN-␥ production mediated by natural killer (NK) and T cells. 20,21 Moreover, IL-1 has been implicated in implantation, 22 and trophoblast growth and invasion.…”
mentioning
confidence: 99%
“…24 Altered IL-1 production may affect the balance of Th1/Th2 cytokine responsiveness, involving either pregnancy success or failure by two potential mechanisms. First, since IL-1␣ and IL-1␤ are important co-stimulators for Th2 cell proliferation, [16][17][18][19] decidual IL-1 may influence Th2 cell generation. Conversely, low IL-1␤ production at the maternal-fetal interface may reduce Th2-type cytokine production, and thus, in concert with elevated decidual IL-12 levels, favor a Th1-type response to the developing conceptus, which could contribute to early pregnancy failure.…”
mentioning
confidence: 99%